Assembly and fabrication considerations of annular linear induction pumps for space nuclear reactors - Carlos O. Maidana (2018)
© 2014, The Author(s). In the design process of liquid metal thermo-magnetic systems in general and of annular linear induction pumps for space applications in particular, special care should be taken with the materials selected, its fabrication and assembly methodology, instrumentation and thermal stresses. The later requires not only a study of the topics mentioned but also an exhaustive quality assurance and quality control mechanism to be in place. The minimum requirements for these systems are 5–7 years with no fail of any type and a lifespan of at least 8 years for fission surface power applications. If the thermo-magnetic system will be part of a nuclear propulsion system its life span and mean time between failures could be increased even more. Obviously secondary/redundancy mechanisms will be in place but each component added will add weight and add an extra element to the risk management consideration. We need to keep clear that maintenance in space is almost impossible and that liquid metals such as NaK78 are reactive to air and water. In this chapter some considerations to the assembly and fabrication are given.